Dimer Stabilization by SpyTag/SpyCatcher Coupling of the Reductase Domains of a Chimeric P450 BM3 Monooxygenase from Bacillus spp. Improves its Stability, Activity, and Purification - Essert, Arabella; Castiglione, Kathrin (Chembiochem : a European journal of chemical biology, 2023)
The vast majority of known enzymes exist as oligomers, which often gives them high catalytic performance but at the same time imposes constraints on structural conformations and environmental conditions. An example of an enzyme with a complex architecture is the P450 BM3 monooxygenase CYP102A1 from Bacillus megaterium. Only active as a dimer, it is highly sensitive to dilution or common immobilization techniques. In this study, we engineered a thermostable P450BM3 chimera consisting of the heme domain of a CYP102A1 variant and the reductase domain of the homologous CYP102A3. The dimerization of the hybrid was even weaker compared to the corresponding CYP102A1 variant. To create a stable dimer, we covalently coupled the C-termini of two monomers of the chimera via SpyTag003/SpyCatcher003 interaction. As a result, purification, thermostability, pH stability, and catalytic activity were improved. Via a bioorthogonal two-step affinity purification, we obtained high purity (94 %) of the dimer-stabilized variant being robust against heme depletion. Long-term stability was increased with a half-life of over 2 months at 20 °C and 80–90 % residual activity after 2 months at 5 °C. Most catalytic features were retained with even an enhancement of the overall activity by 2-fold compared to the P450BM3 chimera without SpyTag003/SpyCatcher003.
CRIS-Team Scopus Importer:2023-12-15
Keywords: CYP102A1; CYP102A3; dimerization; multimeric enzymes; protein engineering